Current Status and Future Trends in Myocarditis Related to the COVID-19 Vaccines: A Visual and Bibliometric Analysis - Zhang, Youao; Wang, Mengjia; Wang, Jieyan (Current Vascular Pharmacology, 2025)
AimsThis study aims to conduct a bibliometric and visual analysis of published studies on myocarditis and coronavirus disease 2019 (COVID-19) vaccines.BackgroundThe widespread epidemic of COVID-19 has caused millions of deaths and profoundly affected the global medical landscape. Studies on COVID-19 vaccination and related myocarditis have also increased significantly.ObjectiveTo analyze the current status and trends of myocarditis and COVID-19 vaccine research by bibliometric and to elucidate research hotspots and frontiers.MethodsBased on the Web of Science Core Collection SCI-Expanded database, we utilize Excel 2019 and visualization analysis tools VOSviewer, Co-Occurrence13.2 (COOC13.2), Citespace, HistCite, and Scimago Graphica for analysis.ResultsOur study encompassed a total of 389 relevant articles, and we observed a consistent upward trend in the number of publications over time, indicating the growing interest in this subject. Among the countries and regions contributing to this body of literature, the United States emerged as the leading publisher, with Harvard Medical School being the most prominent institution associated with these studies. Notably, Matthew E. Oster from the United States emerged as one of the prominent authors in this field. Hotspot research and frontier areas include myocarditis and the different types of COVID-19 vaccines (e.g., mRNA vaccines, adenovirus vector vaccines, inactivated vaccines), the development of new vaccines in reducing the incidence and sequelae of COVID-19 without an increased incidence of myocarditis, and relief of vaccine hesitancy.ConclusionResearch on myocarditis and the COVID-19 vaccines has grown rapidly. Our research results can help researchers grasp the current status of myocarditis related to the COVID-19 vaccine research and find new research directions in the future.
Keywords: COVID-19 vaccines